COMBINATION OF ADMINISTRATION OF PIPPER BETLE AND CURCUMA LONGA AGAINST ALBUS FLUOR IN ADOLESCENT GIRLS IN TAMBAK MAYOR NORTH SURABAYA CITY - Dewi Andriani; Rosari Oktaviana Mahundingan (Journal of Vocational Nursing, 2023)
Introduction: Young women often experience Fluor Albus or vaginal discharge, due to a lack of understanding of reproductive health, especially knowledge of how to handle it. Giving a decoction of Pipper Betle and Curcuma Longa is a non-pharmacological measure to treat Fluor Albus. This study aims to determine the effectiveness of giving a decoction of Pipper Betle and Curcuma Longa on the occurrence of vaginal discharge. Methods: The research used Quasy Experimental with a two-group pre-test post-test approach. This research was conducted with a sample size of 40 respondents who were selected using a quota sampling technique using a questionnaire. The statistical test used is the Wilcoxon Test with Pvalue = 0.05. Results: After intervention for 7 days, the results of the Wilcoxon Pipper statistical test were obtained Betle Ï value = <0.001, while the results of boiling Curcuma Longa obtained Ï value = 0.001, and Mann-Whitney test with a value of Ï = 0.26. So it was concluded that there was the effectiveness of giving Pipper Betle and Curcuma Longa against the occurrence of vaginal discharge. Conclusions: It is hoped that the results of this research will increase insight and become a reference for young women who experience Fluor Albus to be motivated to consume Curcuma Longa and Pipper Betle decoctions effectively.